Makna Kasih Persaudaraan Kristiani: Refleksi Teologis - Spiritual - Praktis - Angelo Luciani Moa Dosi Woda (Jurnal Riset Rumpun Agama dan Filsafat, 2024)
In the midst of fast-paced times and the spread of various views, it feels like people are starting to forget the meaning of Christian brotherhood. It is as if the spirit of loving our fellow brothers and sisters like the Lord Jesus loved us is fading away. Now, modern humans are more likely to be "indifferent" to other people, and feel confident in determining themselves. Is this view true? What are the causes and bad effects of this wrong attitude? Can we overcome this prolonged crisis? What steps should be taken? We learn again to understand and appreciate Christian brotherly love.